Description of a Novel Patch Pump for Insulin Delivery and Comparative Accuracy Evaluation. (July 2022) - Baumstark, Annette; Mende, Jochen; Uchiyama, Joji; Haug, Cornelia; Freckmann, Guido
A new insulin patch pump for continuous subcutaneous insulin infusion was developed. The pump is composed of reusable and disposable parts and operates with a stepping motor. This pump was compared to a patch pump and a durable pump regarding basal rate and bolus accuracy. Using a microgravimetric method, boluses of 0.2 U, 1 U and 7 U, and a basal rate of 1 U/h were tested. For all pumps, bolus accuracy was higher when larger volumes were delivered. While median deviations were similar for all pumps, there were differences in the precision of individual boluses and when regarding basal rate delivery divided into 1-h windows.